Atrial fibrillation in the elderly population: Challenges and management considerations. Issue 4 (24th June 2021) - Salih, Mohammed; Abdel‐Hafez, Osama; Ibrahim, Ramzi; Nair, Rajiv
Abstract: Importance: Atrial fibrillation is the most clinically significant arrhythmia in humans when viewed both from a global and also a national perspective. In the United States, approximately 2.7‐6.1 million people are estimated to have atrial fibrillation. With the aging of the population, this prevalence is on an increasing trend and remains an obstacle to cardiovascular health despite significant advancements specific to cardiovascular disease management. Observation: In this specific group of patients, healthcare utilization is a concern from the public health perspective. Unfortunately, misconceptions dominate clinical decision making; for instance, the avoidance of safe and effective anticoagulation strategies in patients at the highest risk for embolic strokes continues to be widespread in clinical practice and is often based on a skewed assessment of risk versus benefit. Also, when there are contraindications to standard interventions for atrial fibrillation, a clear and nuanced understanding of second‐ and third‐line interventions with proven benefit is often lacking. Conclusions and Relevance: An individualized approach should be followed by physicians when managing atrial fibrillation in the elderly patient, taking into consideration the risk of complications, particularly the embolic stroke and the availability of treatment options for stroke prevention whether through pharmacological anticoagulation or left atrial appendage occluding devices. The following review sets out to clarify these issues. Abstract : Atrial arrhythmia is the most common arrhythmia in the elderly population, and its incidence is increasing. This is particularly important as under treatment and avoidance of anticoagulation can lead to serious consequences and complications.